Worldview, secularisation and identity: The resilient state of Lebanon - Lars Erslev Andersen (Danish Institute for International Studies (DIIS), 2022)
For at least the last seven years, Lebanon has been in a deep economic and political crisis that has sparked several mass demonstrations in the heart of Beirut. Every time demonstrations were joined by up to more than a hundred thousand demonstrators with vast participation from the Lebanese society. None of the demonstrations have succeeded in substantially changing the political system. Manipulations by power elites crushed the demonstrations, pandemic and other reasons kept demonstrations away, but many also lost faith in them and stayed home. Why is that? This article argues that it is necessary to use concepts of the state other than the post-Westphalian Weber concept to understand the structure of Lebanon. It investigates the discourse on secularisation and concludes that it is not the solution to the political crisis. It introduces the concept of worldview and argues that a new relation between state institutions and religious communities is needed to provide new perspectives for Lebanon.
Keywords: 330; Inequality and poverty; History and foreign policy; Peacebuilding and democratization